Theoretical approaches to the classification of the functioning of supply chains - Umirzakova, D.K.; Megits, N. (BUKETOV BUSINESS REVIEW, 2017)
The main idea of this article is the review of the structure of supply chains functioning, the participants of the constituent structure, their relationship formation and functioning levels. The approaches to the concept and essence of the definition of the supply chain with different points of view of the researchers on logistics are highlighted and the author’s definition of the supply chain was given. The formation of a logistics channel from the logistic chain is shown, on the basis of specific participants in the logistic channel. The classification of supply chains, presented by different authors in the structures, in the number of levels, in the distribution processes has been studied. An analysis of the variety of available supply chains allows us to conclude that some characteristics relate to the objectives of supply from what goals and objectives are set for the operation of supply chains. Classification of supply chains also makes it possible to distinguish from the whole variety of types of characteristics that characterize their specificity for certain types of activities and focus on their consideration with a view to improving management efficiency. The review of the classification of supply chains made it possible to systematize them and present them as an author scheme, where the classification is represented by attributes and properties common to each other and the differences between them.